Analisis Teknik Dasar Passing Bawah Bola Voli pada Siswa Ekstrakurikuler di SMP N 1 Cibingbin - Rivaldy, Rivaldy; Firmana, Iif (Indo-MathEdu Intellectuals Journal, 2025)
The research stems from field observations indicating frequent technical mistakes made by students, particularly in aspects such as initial stance, hand placement, and overall body coordination during underhand passing. This study aims to assess the mastery level of the basic underhand passing technique in volleyball among students participating in extracurricular activities at SMP Negeri 1 Cibingbin. A descriptive quantitative approach was adopted, utilizing a survey method to gather data. The sample comprised 14 students who actively engaged in the school’s volleyball extracurricular program, selected using a total sampling technique. Data collection methods involved direct observation and performance-based skill tests focusing on the underhand passing technique. The data analysis technique used is quantitative with a descriptive approach. The results revealed that the majority of students demonstrated a “moderate” level of proficiency, with only a few categorized as having “good” or “poor” skills. Common errors observed included unstable foot positioning, bent elbows, and imprecise ball contact. Key factors influencing the effectiveness of underhand passing included arm muscle strength, body balance, and the player’s self-confidence. In light of these findings, the study recommends the implementation of more systematic and structured training programs that align with the students’ individual needs and abilities.